Unusual presentation of oral pyogenic granulomas: a review of two cases - Parajuli, Ramesh (Clin Case Rep, 2018)
Pyogenic granuloma is a benign vascular neoplasm of the oral cavity that usually presents as a small nodular lesion, the gingiva being the commonest site. Occasionally it occurs at uncommon sites with unusual sizes. Here we describe two cases of oral pyogenic granulomas that had an unusual presentation.